PHYTOCHEMICAL ANALYSIS AND ANTIBACTERIAL ACTIVITY OF ORANGE (Citrus sinensis) PEEL - Musa, D. D.; Sangodele, F.; Hafiz, S. S. (FUDMA JOURNAL OF SCIENCES, 2023)
This research work was carried out to evaluate the antibacterial activity and phytochemical analysis of Citrus sinensis, peels purchased from Dutsin-Ma Wednesday market in Dutsinma town, Katsina state, Nigeria. Thereafter shade-dried at room temperature, reduced to powder with electric blender and powder dried in an oven at 400C for 24 hours afterwards, water and methanol were used as solvents for the extraction of the active components using soxhlet extraction technique. Thereafter, sensitivity testing of each of Staphylococcus aureus and E. coli were carried out using agar diffusion method, while minimum inhibitory concentration of the extracts were determined for each of the isolate at varying concentrations of 200mg/ml, 100mg/ml, 50mg/ml, 25mg/ml, 12.5mg/ml and 6.25mg/ml Aqueous and methanol extract gave a yield of 19 and 15% respectively. The zone of inhibition for citrus peel extract using soxhlet extraction against S. aureus at concentration of 500mg/ml was 16mm; while that of E. coli was 10mm. Results of the phytochemical analysis of methanolic extract of C. sinensis revealed the presence of secondary metabolites such as tannin, flavonoids, reducing sugar, alkaloids, cardiac glycoside as well as the aqueous extract which showed the same thing. For the soxchlet extract it showed steroids, saponin, tannin, flavonoids, reducing sugar and alkaloids
Keywords: Antimicrobial, Extracts, Phytochemical Medicinal Plants, Citrus sinensis